A Study on Stromal Expression of CD10 Marker in Breast Carcinoma and Its Role as a Prognostic Marker in a Tertiary Care Center in South Kerala - K. P. Praveena; Jinu Abraham Glaxon; Aswathy Chandramohan; George Vivek (Archives of Medicine and Health Sciences)
Background and Aims: Breast cancer is one of the leading causes of mortality among women. The aim of our study is to evaluate the stromal expression of CD10 in invasive breast carcinoma and to find its relationship with other prognostic markers such as age, histopathologic grade, estrogen receptor (ER), progesterone receptor (PR), and HER2Neu status. Materials and Methods: A total of 51 cases of breast cancer were included in the study. Representative sections were taken and hematoxylin and eosin staining was done. Immunohistochemistry was performed with ER, PR, Her2neu, and CD10. Stromal expression of CD10 is positive when >10% of stromal cells show cytoplasmic and membranous positivity in invasive breast carcinoma. This will be noted and statistically analyzed with different known prognostic markers of breast carcinoma. Results: Stromal CD10 positivity was seen in 74.5% of cases (45% were strongly positive and 29.5% were weakly positive). 25.5% of cases were negative. Positivity for ER, PR, and HER2, was 58.8%, 35.3%, and 27.5%, respectively. Stromal expression of CD10 was found to be significantly associated with ER negativity (P = 0.001) and PR negativity (P = 0.001). Increasing intensity was noted with few parameters such as postmenopausal status and histologic grade but could not show statistical significance. No correlation was found between CD10 overexpression with respect to the age, tumor size, lymph node positivity status, tumor stage and HER2Neu status. Conclusions: CD10 expression correlated strongly with well-established negative prognostic markers, ER/PR negativity, and higher tumor grade, thus indicating that CD10 can be used as an independent marker indicating poor prognosis. This study highlights the role of stromal CD10 expression in predicting prognosis and the relationship with other prognostic markers. Keeping the role stroma plays in predicting prognosis and tumor response, CD10 can be included as a routine prechemotherapy marker in breast carcinoma. Further studies should be performed to see the role stroma plays in hormonal expression and the usefulness of CD10 to predict treatment failure in breast carcinomas receiving neoadjuvant therapy.